1998
DOI: 10.1002/(sici)1099-0844(1998120)16:4<283::aid-cbf801>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate: pentose cycle and oxidative stress

Abstract: The effect of methotrexate (MTX) and leucovorin (LCV) on pentose cycle enzymes and the activity of enzymes involved in enzyme defence mechanisms against ROS in HeLa cells, were studied. The effect of MTX was also investigated on the cellular levels of glutathione. MTX inhibited the activity of glucose-6-phosphate and 6-phosphogluconate dehydrogenases. The activities of glutathione reductase and gamma-glutamylcysteine synthetase were also inhibited by the drug. No effect was observed on the activities of catala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
87
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 29 publications
11
87
0
1
Order By: Relevance
“…In our study, mirtazapine significantly eliminated the inhibitor effect of methotrexate on GSH production. Studies in the literature have demonstrated that methotrexate reduces the levels of glutathione in liver cells 18 . A methotrexate-associated fall in glutathione levels leads to hepatocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, mirtazapine significantly eliminated the inhibitor effect of methotrexate on GSH production. Studies in the literature have demonstrated that methotrexate reduces the levels of glutathione in liver cells 18 . A methotrexate-associated fall in glutathione levels leads to hepatocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…MTX suppresses the antioxidative system and enhances oxidative stress in many organs (Babiak et al, 1998). Therefore, RJ might have protective and decreasing effect on mucositis and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…MTX produces reactive oxygen species (ROS) and thus causes lipid peroxidation and leads to impairment in mitochondrial function. 15 Neutrophil infiltration and oxidative stress were suggested to cause MTX-induced nephrotoxicity in the rat. 16 Similarly, many nephrotoxic drugs including cisplatin and gentamicin are reported to damage the kidney by the production of ROS.…”
mentioning
confidence: 99%